Social Sustainability, Poverty, and Income : An Empirical Exploration - Cuesta, Jose; Madrigal, Lucia; Pecorari, Natalia (World Bank, Washington, DC, 2022)
Social sustainability is often poorly understood and vaguely defined, despite growing appreciation of its relevance as a concept. This paper advances the empirical understanding of social sustainability by constructing a global database of 71 indicators across 193 countries and 37 territories between 2016 and 2020. The indicators are flexibly clustered around four dimensions—social inclusion, resilience, social cohesion, and process legitimacy—for which measurement indices are constructed. A simple empirical analysis using the database confirms that social sustainability is positively and strongly associated with per capita income, negatively and strongly associated with poverty, and negatively but weakly associated with income inequality. Much remains to be analyzed to understand the interactions between dimensions, but the results underscore that social sustainability matters not only in itself, but also to reduce poverty. Furthermore, extending access to markets, basic public services, and social assistance needs to be complemented with strengthening process legitimacy and social cohesion if inequality is to be reduced.